Phytochemical Evaluation, Antimicrobial Activity of Selected Indigenous Plant Ethanolic Extracts and ADMET Properties of its Phytocompounds - Abilasha , D.; Palanisamy, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The scientific investigation was made to study the phytochemical and antimicrobial analysis of ethanoic extract of some indigenous plants and ADMET properties of its phytocompounds. We investigated 27 active phytochemical components in ethanolic extracts of four medicinal plants: Andrographis paniculata, Centella asiatica, Psidium guajava, and Solanum trilobatum. The extracts were subjected to a standard procedure of qualitative phytochemical screening. The phytocompounds in the leaf extracts of the selected plants were identified using IR and GC-MS spectroscopy. The extracts were then tested for in vitro antibacterial activity against Gram-positive (Staphylococcus aureus and Enterococcus) and Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli), as well as antifungal activity against Candida albicans and Aspergillus flavus, using Agar-diffusion methods and reference drugs Amikacin and Nystatin. Psidium guajava ethanol extract was found to be the most efficient against Enterococcus, with an inhibition area of 19 mm when compared to Amikacin. Centella asiatica showed a 13 mm zone of inhibition against Candida albicans, which is comparable to Nystatin's 15 mm zone. Molecular docking experiments revealed that Andrographis paniculata's Stigmasterol (-9.3 kcal/mol) is a good inhibitor of Staphylococcus (PDB:3FYM), and Lupeol (-9.6 kcal/mol) is a promising inhibitor of Candida albicans (PDB:4HOF). Both showed binding energies equivalent to common antibiotics amikacin (-7.2 kcal/mol) and nystatin (-8.6 kcal/mol).